Pedagogical Approaches For Intercultural Awareness: A Qualitative Inquiry Into EFL Teaching Practice In Bima - Hadijah, Hadijah; Dollah, Syarifuddin; Munir, Munir (ELS Journal on Interdisciplinary Studies in Humanities, 2026)
Intercultural awareness is becoming important in English as a Foreign Language (EFL) teaching, especially students will interact with people from different cultural backgrounds in the future. However, This gap can be understood through the lens of intercultural communicative competence (ICC) proposed by Michael Byram, which emphasizes not only linguistic skills but also attitudes, knowledge, and skills for interpreting and relating across cultures. This study investigates how five EFL teachers in Bima integrate cultural elements into their lessons and challenges in their teaching. A qualitative approach was used, involving classroom observations, interviews, and an analysis of lesson documents. The findings show that teachers do include cultural ideas in their teaching, but these moments are usually brief and not fully developed. Teachers often begin with local cultural to help students understand the cultures from other countries, and they adjust their teaching based on students’ reactions. Despite their efforts, teachers face several difficulties, such as students’ limited exposure to global cultures, strict curriculum requirements, sensitive cultural issues, and a lack of training and appropriate materials. Overall, the study shows that intercultural teaching in Bima is present but it does not consistent or deeply developed. More support, training, and resources are needed to help teachers promote intercultural awareness more effectively.